The effect of a six-week plyometric training performed with different set configurations on explosive performance: cluster vs. traditional set configurations - Yilmaz, N.; Alemdaroglu, U.; Köklü, Y.; Türkdogan, H.; Asçi, A. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: The aim of this study was to compare the effects on jump, sprint and change of direction performance of a 6-week plyometric training performed using two different set configurations. METHODS: Twenty-five male soccer players (age 15.04±0.84 years; height 172.3±6.3 cm; weight 56.18±8.7 kg) from the same U16 team of a professional club voluntarily participated in the study. Countermovement jump (CMJ), squat jump (SJ), standing long jump (SLJ), zigzag agility test, 10 m and 20 m sprint performance tests were carried out in the week before and the week after the 6-week plyometric training period. After pretests, players were allocated to the cluster (CLS; N.=9), traditional (TRD; N.=8), or control groups (CON; N.=8) according to pretest results. RESULTS: The results of this study show that the CLS group had significantly greater improvements than the CON group in all tests except the zigzag test, while the TRD group showed significant improvement in sprint tests, SJ and SLJ compared to the CON group (p <0.05). Also, both CLS and TRD groups had significantly better performance in post-test than in pre-tests in all cases except for the TRD group Zigzag test. CONCLUSIONS: We conclude that coaches may be advised to use the CLS set configuration since it is as effective as traditional methods, but poses lower risk in terms of performance decrement and injury due to fatigue and technical deformations.